Migrant mothers’ everyday practices in nurseries and kindergartens as a strategy for social integration. - Stratigaki, Maria; Vaiou, Dina (The Greek Review of Social Research, 2007)
<div style="font-size: 13.4949px; font-family: serif; left: 111.784px; top: 402.063px; transform: rotate(0deg) scale(0.97844, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="466.4550269603729">Access to nurseries and kindergartens for children of migrant domestic workers is a <div style="font-size: 13.4949px; font-family: serif; left: 111.784px; top: 421.482px; transform: rotate(0deg) scale(0.980469, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="466.70318697471623">dual path to social integration: (a) it is a condition for their integration into the labour <div style="font-size: 13.4949px; font-family: serif; left: 111.784px; top: 440.9px; transform: rotate(0deg) scale(0.95459, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="466.7625869781494">market: their children’s access to nurseries and kindergartens and the conditions under <div style="font-size: 13.4949px; font-family: serif; left: 111.785px; top: 460.304px; transform: rotate(0deg) scale(0.979229, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="466.8312269821167">which this is possible to a large extent determine the mothers’ prospects of getting a <div style="font-size: 13.4949px; font-family: serif; left: 111.785px; top: 479.723px; transform: rotate(0deg) scale(1.0143, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="466.57646696739204">paid job, (b) it shapes their perspectives on long-term settlement, which becomes <div style="font-size: 13.4949px; font-family: serif; left: 111.785px; top: 499.141px; transform: rotate(0deg) scale(0.957988, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="466.76390697822575">contingent on their children’s performance at school. This paper discusses formal and <div style="font-size: 13.4949px; font-family: serif; left: 111.785px; top: 518.56px; transform: rotate(0deg) scale(1.0348, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="466.69262697410585">informal practices related to access to nurseries and schools, as well as migrant <div style="font-size: 13.4949px; font-family: serif; left: 111.786px; top: 537.978px; transform: rotate(0deg) scale(1.03707, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="466.68074697341916">mothers’ reactions to xenophobic attitudes and behaviour by teachers and other <div style="font-size: 13.4949px; font-family: serif; left: 111.786px; top: 557.397px; transform: rotate(0deg) scale(0.965754, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="466.6847069736481">children. Migrant working mothers seem to be determined to fight for their children’s <div style="font-size: 13.4949px; font-family: serif; left: 111.786px; top: 576.815px; transform: rotate(0deg) scale(1.03286, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="466.8536669834137">access to nurseries and schools. Their strong commitment to achieving the best <div style="font-size: 13.4949px; font-family: serif; left: 111.786px; top: 596.234px; transform: rotate(0deg) scale(0.944433, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="466.7705069786072">possible childcare on the one hand reflects traditional gender roles (it is women’s rather <div style="font-size: 13.4949px; font-family: serif; left: 111.786px; top: 615.652px; transform: rotate(0deg) scale(0.991706, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="467.3249070106505">than men’s task to find care facilities) and on the other contributes to strengthening <div style="font-size: 13.4949px; font-family: serif; left: 111.787px; top: 635.056px; transform: rotate(0deg) scale(0.934153, 1); transform-origin: 0% 0% 0px;" dir="ltr" data-angle="0" data-font-name="g_font_126_0" data-canvas-width="272.77273576583855">their role in the household vis-à-vis their husbands.